Do Thoracic Spinal Deformities Affect Outcomes of Spinal Cord Stimulators: A Retrospective Chart Review. Issue 3 (1st February 2021) - Malige, Ajith; Kantzos, Andrew; Sokunbi, Gbolabo O.
Abstract : Study Design: Retrospective chart review. Objective: The aim of this study was to ascertain whether the presence of structural thoracic deformities affects outcomes of permanent SCS placement. Summary of Background Data: Neural modulation via spinal cord stimulators (SCSs) has become an accepted treatment option for various chronic pain syndromes. In most cases, the surgeon desires accurate midline positioning of the paddle lead, allowing for flexibility of unilateral or bilateral coverage of pain patterns. Structural spinal deformities (scoliosis or kyphosis) often result from coronal, sagittal, and rotatory deformity that can make midline placement more difficult. Methods: Between 2013 and 2017, two-hundred forty-one charts of patients who underwent permanent SCS placement at our suburban hospital were reviewed. Demographic information, numerical rating system (NRS) pain scores, Oswestry Disability Index (ODI) scores, and opioid medication usage were recorded at baseline and after permanent stimulator placement. Thoracic scoliosis and kyphosis angles were measured using spinal radiographs. The effect of each structural deformity on NRS, ODI, and narcotic medication usage changes from baseline was analyzed. Results: Overall, 100 patients were included in our cohort. Fifty-six patients had measured thoracic spinal deformities (38% with scoliosis, 31% with kyphosis). There was no significant difference in NRS scores, ODI scores, or narcotic usage change between patients with scoliosis and those without ( P  = 0.66, P  = 0.57, P  = 0.75) or patients with kyphosis and those without ( P  = 0.51, P  = 0.31, P  = 0.63). Bivariate linear regression analysis showed that scoliotic and kyphotic angles were not significant predictors of NRS ( P  = 0.39, P  = 0.13), ODI ( P  = 0.45, P  = 0.07), and opioid usage ( P  = 0.70, P  = 0.90) change, with multivariate regression analyses confirming these findings. Conclusion: SCSs can be effective options for treating lumbar back pain and radiculopathy. Our study suggests that the presence of mild structural deformities does not adversely affect outcomes of permanent SCS placement and as such should not preclude this population from benefiting from such therapies. Level of Evidence: 4 Abstract : This study looks to ascertain whether the presence of structural thoracic deformities affects outcomes of permanent SCS placement. Spinal cord stimulators can be effective options for treating lumbar back pain and radiculopathy, even in patients with mild structural deformities such as thoracic scoliosis or kyphosis.